Experiences of pre-service teachers in high-stakes assessments: implications for teacher education - Mary Cris J. Go; Jovelyn G. Delosa (Journal of Education and Learning (EduLearn), 2026)
Teacher readiness for high-stakes assessments is a critical but underexplored area, especially given the challenges of low passing rates and insufficient preparation strategies. Literature shows studies emphasizing student readiness and performance, but less attention is given to the specific preparation, support mechanisms, and professional development for teachers regarding high-stakes assessments. This study aimed to examine pre-service teachers’ experiences in preparing for high-stakes assessments and identify key factors that influence their readiness. Using an interpretative phenomenological analysis (IPA) approach, data were gathered from semi-structured focus group discussions (FGDs) with seven graduating teacher education students. The analysis revealed five key themes: preparation strategies, essential competencies, concerns and fears, access to resources, and institutional support. These factors were identified as crucial to shaping students’ preparedness. The study concluded that targeted institutional interventions such as enhanced mentoring, improved access to resources, and stronger support systems are essential for improving teacher readiness. Recommendations included integrating holistic preparation strategies into teacher education curricula and fostering institutional support networks. This research contributed to the global discourse surrounding the experiences of pre-service teachers, proposing the need for design-thinking-based innovations to establish the readiness of pre-service teachers in taking high-stakes assessments, which defines their initial entry into the teaching profession.